Technical Note: Robust individual thermoluminescence dosimeter tracking using optical fingerprinting. Issue 1 (19th November 2019) - Shang, Daili; Gu, Wenbo; Landers, Angelia; Woods, Kaley; Yu, Victoria; Neph, Ryan; Tenn, Stephen; Sheng, Ke
Abstract : Purpose: The thermoluminescence dosimeter (TLD) has desirable features including low cost, reusability, small size, and relatively low energy dependence. However, the commonly available poly‐crystal TLDs (e.g., TLD‐100) exhibit high interdetector variability that requires individual calibration for high detection accuracy. To improve individual TLD tracking robustness, we developed an optical fingerprinting method to identify the TLD‐100 chips. Methods: Seven hundred and fifty‐two images were initially captured using a digital microscope camera to build a feature library for both facets of 376 TLD‐100 chips. A median intensity thresholding method was used to segment images into foreground and background. The affine transformation was used to register the segmented images to the same position. The fingerprint of each image was calculated from its registered image. All fingerprints were then recorded in an Elasticsearch® search database. The TLD fingerprint match was tested three times when the library was established and repeated once 20 months later. All chips were irradiated at 0, 1, 4, and 8 Gy on a calibrated clinical MV linac to establish the individual calibration curve. Results: The true positive rate of identifying TLDs based on their optical fingerprints was 100% at initialization of the inventory. After 20 months and multiple deployments for characterization, calibration, and dose measurement, the true positive match rate dropped to 99% with zero false‐positive matches. The TLDs exhibited high self‐consistency in the dose–response test with R 2 between 0.988 and 1 with linear regression. Conclusions: The TLD‐100 chips surface textures are unique and sufficient to support accurate identification based on the optical fingerprinting. This method provides inexpensive and robust management of the TLDs for individual calibration and dosimetry.